The effectiveness of loyalty marketing programmed through real rewards trough customer relationship at Carrefour Subang Jaya / Dina Azua Ahmad Musa - Ahmad Musa, Dina Azua (Faculty of Business and Management, 2008)
The number one retailer in Europe and the second-largest retailer in the world is Carrefour. In Malaysia, Carrefour is a leading hypermarket chain selling a wide range of household grocery products ranging from frozen goods and fresh products to textiles, garments and shoes, as well as electrical goods such as home kitchen items and audio-visual appliances. Carrefour is widely recognized as a convenient one-stop shopping centre that caters to a mix of consumers from homemakers to students and working professionals.